Safety Management Practices in the Bhutanese Construction Industry - Dorji, Kin; Hadikusumo, Bonaventura H. W. (Penerbit Universiti Sains Malaysia, 2006)
The construction industry is considered as one of the most hazardous industrial sectors wherein the construction workers are more prone to accidents. In developed countries such as United Kingdom and United States of America, there is strict legal enforcement of safety in the construction industry and also in the implementation of safety management systems which are designed to minimize or eliminate accidents at work places. However, occupational safety in construction industry is very poor in developing countries such as Bhutan. This study investigates the prevalent safety management practices and perceptions in the construction industry in Bhutan. The study was conducted among 40 construction contractors and 14 government officials through method of questionnaire survey, interview and discussion. The results of the study revealed that there are many occupational safety problems in the construction industry in Bhutan, problems such as lack of safety regulations and standards, low priority of safety, lack of data on safety at construction sites, lack of competent manpower, lack of safety training, lack of safety promotion, and lack of documented and organized safety management systems. Furthermore, the study also proposes some recommendations for safe construction in Bhutan.